Neuroarchitectural Design Element Implication on Student-Athlete School with Holistic Athlete Development - Muhamad Refi Fauzan Akbar; Iwan Sudradjat (Jurnal Teknik Indonesia, 2026)
The physical and cultural environment we create influences our thinking, emotions, and behavior. Architecture plays a role in shaping us as humans, contributing to human well-being. Architecture is a built environment inhabited by humans and engaged in activities within it. Architectural manifestations are always rooted in the physical body, and architectural design has the capacity to nurture, stimulate, or even destroy these through the influences that emerge from/impact human perception patterns and experiences of the space. The International Olympic Committee recommends that youth athlete development programs focus on athletes' health, ability, and resilience, along with broad, inclusive, sustainable, and enjoyable achievement. The term "dual career" globally represents a solution to the challenge of balancing sport and education for young athletes. The "holistic whole-person" approach was introduced as a solution to the "dual-career" problem3. supported by essential features in the youth athlete development environment4. To support a "holistic whole-person" program, considerations should address psychosocial, psychological, and academic aspects5. This is reinforced by the long-term and short-term impacts experienced by student athletes, including psychological (self-optimization), psychosocial (life skills), and educational (academic) impacts, in addition to physical (fitness and/or injury) impacts6. This effort demands the presence of architecture in the creation of the built environment (in this context, a special athlete school), both indoor and outdoor, where athletes are required to deliver optimal performance (during their training process) over a certain period of time while living and undergoing training in that environment. Given this situation, the question arises, "What is the architectural design strategy for creating a spatial experience (holistic brain and body performance through user impressions presented by architectural expression) to optimize athlete performance in a student-athlete school?" based on this, it is felt that there is a need to present a model architecture as a design guideline for a Student-athlete School, which is hoped to generally represent the role of architecture in accommodating the needs of optimizing athlete performance in a Student-athlete school.